2007
DOI: 10.1190/1.2435200
|View full text |Cite
|
Sign up to set email alerts
|

Crossline resistivity tomography for the delineation of anomalous seepage pathways in an embankment dam

Abstract: Crossline resistivity tomography was developed to find out anomalous seepage pathways in an embankment dam. By applying crossline tomography to the investigation of embankment dams, leakage pathways can be effectively located because the crossline tomogram presents resistivity distribution in the horizontal plane of an embankment dam. To test the effectiveness of crossline tomography, we applied it to data from an experiment designed to delineate anomalous seepage pathways in the embankment dam. The method yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 25 publications
0
48
0
Order By: Relevance
“…porous or fractured zones). This technique is widely used to detect voids [37][38][39][40][41], underground water [42][43][44], fractural zone recognition [45][46][47][48][49][50][51][52][53][54][55][56][57], and mineral exploration [58,59]. The difference in resistivity between the target and its surrounding materials is a key factor to ensure this technique is viable.…”
Section: Electric Resistivitymentioning
confidence: 99%
“…porous or fractured zones). This technique is widely used to detect voids [37][38][39][40][41], underground water [42][43][44], fractural zone recognition [45][46][47][48][49][50][51][52][53][54][55][56][57], and mineral exploration [58,59]. The difference in resistivity between the target and its surrounding materials is a key factor to ensure this technique is viable.…”
Section: Electric Resistivitymentioning
confidence: 99%
“…Images of subsurface bulk electrical resistivity can therefore be used to help assess geologic units that may be more likely to conduct seepage through foundation or embankment materials, or to map regions of increased saturation. Numerous resistivity studies have focused on both internal erosion detection (Cho and Yeom, 2007;Kim et al, 2007;Sjö dahl et al, 2005Sjö dahl et al, , 2008 as well as identification of seepage pathways associated with dam foundation materials (Abu-Zeid, 1994;Di and Wang, 2010;Panthulu et al, 2001).…”
Section: Self-potentialmentioning
confidence: 99%
“…Previous geophysical studies have demonstrated the utility of using electrical resistivity methods to detect and characterize the seepage conditions occurring at dams [7]. Dahlin and Johansson [8], Johansson and Dahlin, [5], Aal et al [6] and Cho and Yeom [9], had earlier applied this method to study the embankment of dams. Benson et al [10] had also applied it successfully to the detection of buried wastes and wastes migrations.…”
Section: Introductionmentioning
confidence: 99%